2020
DOI: 10.1063/5.0005425
|View full text |Cite
|
Sign up to set email alerts
|

Using single-electron box arrays for voltage sensing applications

Abstract: Single-electron tunneling transistors (SETs) and boxes (SEBs) belong to the family of charge-sensitive electronic devices based on the phenomenon of Coulomb blockade. An SEB is a two-terminal device composed of “leaky,” Cj, and “non-leaky,” Cg, nanoscaled capacitors in series. At low temperatures, the charge at the common node is quantized and can only be changed near energy-population degeneracy points, resulting in periodic oscillations of the SEB admittance as a function of voltage applied to Cg. In compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As shown theoretically in Section 2 and confirmed experimentally in Section 5.1, the SNR for the reflectometry response of a single SEB is low due to very small magnitude of admittance oscillations caused by single electron charging even if an optimized MN described in Section 3 is used. Recently, we have demonstrated that for small SEBA SNR scaling by a factor N is achievable [33]. To study the sensitivity trends in SEBA with resolvable individual characteristics, we performed a detailed study of a small array nominally composed of four SEBs and controlled by two gates in the range of temperatures from 0.3 to 30 K. Post-experimental SEM image of the array is presented in Figure 10a.…”
Section: Characterization Of a Small (N = 3) Sebamentioning
confidence: 99%
See 1 more Smart Citation
“…As shown theoretically in Section 2 and confirmed experimentally in Section 5.1, the SNR for the reflectometry response of a single SEB is low due to very small magnitude of admittance oscillations caused by single electron charging even if an optimized MN described in Section 3 is used. Recently, we have demonstrated that for small SEBA SNR scaling by a factor N is achievable [33]. To study the sensitivity trends in SEBA with resolvable individual characteristics, we performed a detailed study of a small array nominally composed of four SEBs and controlled by two gates in the range of temperatures from 0.3 to 30 K. Post-experimental SEM image of the array is presented in Figure 10a.…”
Section: Characterization Of a Small (N = 3) Sebamentioning
confidence: 99%
“…Note that the spacing between lines in each SEB along the V g sens axis is almost the same, while along the V g tune axis it is distinctly different, indicating dissimilar capacitance C g tune for each SEB. To achieve weak and dissimilar coupling tuning gate can be simply positioned on the side of the array [33]. This combination ensures the appearance of line crossings within an easily accessible span of V g tune .…”
Section: Characterization Of a Small (N = 3) Sebamentioning
confidence: 99%